Jurisprudence in the Stories of David and Sulaiman - Peace Be Upon Them - from Qur'an - Ababneh, Ahmad; Alsouri, Kefah; Jarrah , Mashal (Dirasat: Shari'a and Law Sciences, 2020)
The research aims to explain the judicial rulings considered in the stories of David and Suleiman, peace be upon them, in particular, stating the following rules of the participation of 2 judges in one issue, the existence of many judges in one country, and the multiple decisions taken regarding one issue. The study used the analytical approach to study the provisions of the Qur'an deduced from the stories of Dawoud and Sulaiman - peace be upon them - in the Al-Anbiya and Saad Surahs, which are the basis of various provisions in the jurisprudence of the judiciary. The study found that the participation of judges in the same issue is permissible, the meeting of more than one judge in one place and even in one jurisdiction is permissible, Suleiman was a judge like David and they met, the judgment of the judiciary may be multiple in one issue, then there will be more than one correct judgment, and the judge may rule on what he deems most likely and most favorable for the case of the opponents. The study recommended the need to refer to the provisions of the Holy Quran in various sections of jurisprudence. It also recommended the need to conduct studies based on Quranic stories, which occupied a quarter of the verses of the Holy Quran, to deduce the benefits and judgments of various subjects.